Boffin Boy and the Red Wolf - Orme, David, 1948 Mar. 1-; Richardson, Peter (Watlington, Oxon : Ransom, 2006)
Boffin Boy, fourteen-year-old Rick Shaw's superhero alterego, must work fast to keep the evil Red Wolf from using television to steal magic and money from the world's wizards.
2.0
3-6
Keywords: Good and evil -- Comic books, strips, etc. -- Juvenile fiction; Heroes -- Comic books, strips, etc. -- Juvenile fiction; Space and time -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Good and evil -- Fiction; Heroes -- Fiction; Science fiction; Space and time -- Fiction; Comic books, strips, etc; Good and evil -- Comic books, strips, etc. -- Fiction; Heroes and heroines -- Comic books, strips, etc. -- Fiction; Science fiction comic books, strips, etc; Space and time -- Comic books, strips, etc. -- Fiction; Superhero comic books, strips, etc; Graphic novels; Science fiction comic books, strips, etc; Superhero comic books, strips, etc